Appointment attendance and patient perception of drive‐up INR testing in a rural anticoagulation clinic during the COVID‐19 pandemic. Issue 4 (20th January 2021) - Zobeck, Bryan; Carson, Erin; MacDowell, Martin; Hunt, Aaron; Reeder, Austin
Abstract: Introduction: The Anticoagulation Forum and Centers for Disease Control and Prevention (CDC) recommend drive‐up international normalized ratio (INR) testing to combat INR non‐adherence and increase safety during the coronavirus disease 2019 (COVID‐19) pandemic. Patient perceptions and impact on attendance have not been studied. Objective: To assess appointment volume and patient perception after initiation of drive‐up INR testing in a rural pharmacist‐managed anticoagulation clinic. Methods: This cross‐sectional cohort survey study offered each patient attending the anticoagulation clinic via drive‐up or in‐office visit a survey between May 27 and July 2, 2020. Patients testing off‐site were excluded. Study end points included monthly patient volume, visit type preference, testing barriers, desired drive‐up duration, and overall clinic satisfaction. Clinic appointment volume from October 2019 to June 2020 was collected retrospectively through a schedule review. Results: Sixty‐four (80%) of 80 surveys offered were completed: 46.6% of respondents preferred drive‐up testing, 26.7% indifferent, and 26.7% preferred in‐office visits; 38.7% of respondents indicated a greater likelihood of continuing routine INR monitoring via drive‐up testing. Of the respondents completing the survey curbside, 46% and 27% of respondents identified reduced COVID‐19 transmission risk and ease of transportation as benefits of drive‐up INR testing, respectively. March and April clinic volumes were 19% and 22% below average, respectively, returning to baseline after drive‐up testing was implemented. Clinic rating before and after drive‐up testing remained high at 2.75 on a scale of 0‐3. While infection risk was identified as the biggest barrier to care by 32.8% of respondents, 59.3% of all respondents wanted drive‐up testing to continue indefinitely. Conclusions: Drive‐up INR testing improves patient attendance during the COVID‐19 pandemic. Patient perception of drive‐up testing is positive. About 46% of respondents preferred drive‐up INR testing with telehealth follow‐up and 59.3% of respondents want drive‐up testing to continue indefinitely, which suggests this approach to INR testing as a potential method to allay barriers to routine monitoring beyond the scope of the pandemic.